The Indigo Molecule Revisited Again: Assessment of the Minnesota Family of Density Functionals for the Prediction of Its Maximum Absorption Wavelengths in Various Solvents - Francisco Cervantes-Navarro; Daniel Glossman-Mitnik (Journal of Chemistry)
The Minnesota family of density functionals (M05, M05-2X, M06, M06L, M06-2X, and M06-HF) were evaluated for the calculation of the UV-Vis spectra of the indigo molecule in solvents of different polarities using time-dependent density functional theory (TD-DFT) and the polarized continuum model (PCM). The maximum absorption wavelengths predicted for each functional were compared with the known experimental results.